Рецепція літературної творчості Г. Хоткевича дослідниками XX століття - Лаврик, О.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2005)
В статье рассматриваются оценки литературного творчества Г. Хоткевича исследователями XX века. Анализ проводится с учетом общественно-культурной ситуации в Украине. The appraisals given by researchers of XX century to G.Hotkevych's literary works are considered in the article. The social and cultural situation in Ukraine is taken into consideration.
Keywords: Хоткевич; модерніст; модернізм